Pre-existing mental disorder, clinical profile, inpatient services and costs in people hospitalised following traumatic spinal injury: a whole population record linkage study. Issue 3 (15th May 2020) - Sharwood, Lisa Nicole; Wiseman, Taneal; Tseris, Emma; Curtis, Kate; Vaikuntam, Bharat; Craig, Ashley; Young, Jesse
Abstract : Background: Risk of traumatic injury is increased in individuals with mental illness, substance use disorder and dual diagnosis (mental disorders); these conditions will pre-exist among individuals hospitalised with acute traumatic spinal injury (TSI). Although early intervention can improve outcomes for people who experience mental disorders or TSI, the incidence, management and cost of this often complex comorbid health profile is not sufficiently understood. In a whole population cohort of patients hospitalised with acute TSI, we aimed to describe the prevalence of pre-existing mental disorders and compare differences in injury epidemiology, costs and inpatient allied health service access. Methods: Record linkage study of all hospitalised cases of TSI between June 2013 and June 2016 in New South Wales, Australia. TSI was defined by specific International Statistical Classification of Diseases and Related Health Problems, Tenth Revision, Australian Modification (ICD-10-AM) codes. Mental disorder status was considered as pre-existing where specific ICD-10-AM codes were recorded in incident admissions. Results: 13 489 individuals sustained acute TSI during this study. 13.11%, 6.06% and 1.82% had pre-existing mental illness, substance use disorder and dual diagnosis, respectively. Individuals with mental disorder were older (p<0.001), more likely to have had a fall or self-harmed (p<0.001), experienced almost twice the length of stay and inpatient complications, and increased injury severity compared with individuals without mental disorder (p<0.001). Conclusion: Individuals hospitalised for TSI with pre-existing mental disorder have greater likelihood of increased injury severity and more complex, costly acute care admissions compared with individuals without mental disorder. Care pathway optimisation including prevention of hospital-acquired complications for people with pre-existing mental disorders hospitalised for TSI is warranted.